Clinical Profile and Outcome of COVID 19 Patients at Tertiary Cardiovascular Center of Nepal. - Sherpa, Kunjang; Manandhar, Reeju; Adhikari, Chandra Mani; Dhungana, Murari; Prajapati, Dipanker; Raut, Roshan; Acharya, Kiran; Bogati, Amrit; Shrestha, Battu Kumar; Joshi, Surakshya; Bajracharya, Prashant; Dangol, Prati Badan; et al. (Nepalese Heart Journal, 2021)
Background and Aims: Cardiovascular comorbidities are common in patients with COVID-19 and these patients are at higher risk of morbidity and mortality. It is not known if the presence of cardiovascular co-morbid conditions poses independent risk or whether this is mediated by other factors. Methods: This is a retrospective follow up study done at Shahid Gangalal National Heart Centre (SGNHC). The main objective of this study was to study the clinical profile, baseline comorbidities, and outcome of cardiac patients and health care worker diagnosed with COVID 19. This study retrospectively evaluated case records of all cardiovascular disease (CVD) patients admitted at SGNHC with COVID 19 cases from 1st case diagnosed on July at SGNHC till September 2020. Results: During this study period, 90 patients with COVID 19 with cardiovascular disease were admitted. The mean age of the study population was 52.3±19 years with 65.6% being male. Among the study population 52 (57.8%) had past history of cardiovascular disease, hypertension in 18 (20%) cases, diabetes in 8 (8.9%) cases. Among the patients with cardiovascular diagnosis, acute coronary syndrome was most common cardiovascular diagnosis in 23 (25.6% cases) followed by rheumatic heart disease in 21 (23.4%) cases, dilated cardiomyopathy in 7 (7.8% cases), ischemic cardiomyopathy with reduced ejection fraction (EF) in 7 (7.8%) cases, post coronary artery bypass graft (CABG) in 8 (8.9%), post valve replacement in 5 (5.5%), congenital heart disease in 3.3% cases and complete heart block in 3.3% cases. Most of the cases were symptomatic with moderate illness in 46.7% cases, mild illness in 41.4% cases and severe/critical illness in 11.1% cases. Among COVID patients with cardiovascular disease, the mortality was 11.1%. Conclusion: Patients with cardiovascular disease with COVID 19 have more severe COVID 19 symptoms and has higher COVID 19 related death, so strict vigilance and early intervention is needed to improve its outcome.